Aggregate Feeding by the Copepods Calanus and Pseudocalanus Controls Carbon Flux Attenuation in the Arctic Shelf Sea During the Productive Period - van der Jagt, Helga; Wiedmann, Ingrid; Hildebrandt, Nicole; Niehoff, Barbara; Iversen, Morten H. (Frontiers in Marine Science, 2020)
Up to 95% of the oceanic primary production is recycled within the upper few hundred meters of the water column. Marine snow and zooplankton fecal pellets in the upper water column are often recycled at rates exceeding those measured for microbial degradation, suggesting that zooplankton might be important for flux attenuation of particulate organic carbon in the upper ocean. However, direct evidence for interactions between zooplankton and settling aggregates are still rare. We investigated the importance of zooplankton aggregate feeding for carbon flux attenuation in the upper ocean by determining aggregate ingestion rates and feeding behavior on settling aggregates by the dominant Arctic filter-feeding copepods Calanus spp. and Pseudocalanus spp. Both genera were observed to detect and feed on settling aggregates. Using in situ zooplankton and aggregate abundances in combination with the measured aggregate feeding rates, we calculated that 60–67% of the total carbon flux attenuation at three Arctic locations could be explained by Calanus spp. and Pseudocalanus spp. aggregate feeding alone. When including microbial degradation of the settling aggregates, we could explain up to 77% of the total carbon flux attenuation. Our results suggest that by directly ingesting and fragmenting settling marine snow, mesozooplankton are key organisms for flux attenuation in Arctic waters.